Ações colaborativas em aulas de educação física: possibilidades inclusivas para os alunos público-alvo da educação especial - Carvalho, Ingrid Rosa (2022)
The research aims to understand and discuss the possibilities of collaborative actions for the process of including the target audience of special education in Physical Education classes. More specifically, it intends to contextualize the cross-relationships in the inclusive processes of this public in the investigated school and to problematize, in the collaborative-critical perspective of action research, the movements that engender the inclusive processes produced with the collaborating teachers, the regent teacher, the pedagogue and to the Physical Education teacher. This is a qualitative, descriptive and exploratory research, based on the dynamics of collaborative-critical action research, whose epistemological perspective promotes changes in educational contexts, based on co-responsibility actions, adopting, as the central axis of the established dynamics, the goal - a critical-reflective look at oneself and the context involved. The research was carried out in a public elementary school, located in the municipality of Cariacica, and had the participation of the school team that composed the collective researcher, with the two collaborating teachers, the Physical Education teacher, the caregiver, the pedagogue, the director and the researcher. In that institution, basic education is offered, with the modalities of elementary education I and Youth and Adult Education. The intervention process and data collection were carried out in the second half of 2019, with information produced and recorded through the following instruments: semi-structured interview with the institution's professionals - part of the collective researcher -, in addition to a roaming diary with records produced by participant observation and audiovisual recordings. In 2020, the data were transcribed and organized, going through the process of categorical content analysis, a moment that went through the pre-analysis period, when the floating reading and selection of documents to be analyzed, as well as the formulation of hypotheses and the preparation of the material, which was explored, coded and categorized with clippings from the units, with the results interpreted by inference. From the spiral approach, it was possible to empower and qualify inclusive training movements, committed to the transformation of the investigated reality, and to create opportunities for the active social participation of all students. The results indicate that the experience of working from the perspective of collaborative teaching allows the expansion and resignification of objective and subjective knowledge in relation to pedagogical practice in an inclusive perspective, enhancing the participation of the target audience of special education with other students without disabilities or disorder. The inclusive movements produced collectively revealed the work in co-teaching as a real possibility of pedagogical success through the sharing of theoretical and practical knowledge among the work team, thus contributing to the improvement of the learning of all students, through the expansion of related knowledge. to different forms of teaching that aim at common goals: the quality of teaching and the equity of educational opportunities for all students.